Localization of membrane-associated carbonic anhydrase type IV in kidney epithelial cells. - Brown, D (1990)
Rat carbonic anhydrase (CA) IV was purified by affinity chromatography and used to produce a specific antiserum in rabbits for immunolocalization studies in rat kidney. CA IV was localized in apical plasma membranes of the proximal convoluted tubule and the thick ascending limb of Henle. Both of these segments are involved in bicarbonate reabsorption in the rat. Immunofluorescent staining of the brush border was faint in the S1 segment, greatest in the S2 segment, and absent from the S3 segment of the proximal tubule. CA IV was also detected in the basolateral plasma membrane of proximal-tubule and thick-ascending-limb epithelial cells by immunofluorescence and immunoelectron microscopy. In the proximal tubule, an extracellular membrane CA had been previously suggested on the basis of electrophysiological studies. CA IV was not detected in intercalated cells of the collecting ducts. These cells contain, in contrast, abundant cytosolic CA II. Thus, the distribution of CA IV is quite distinct from that of CA II; it corresponds with the localization of an isoenzyme(s) that did not stain with antibodies against CA II but that was revealed by histochemical-staining procedures. We conclude that the apical CA IV is the luminal CA responsible for bicarbonate reabsorption in the proximal tubule and the thick ascending limb in the rat kidney. These studies also suggest that CA IV plays a role in bicarbonate transport across the basolateral plasma membrane in these two segments of the rat nephron.